2017
DOI: 10.1016/j.chom.2016.12.004
|View full text |Cite
|
Sign up to set email alerts
|

The Bacterial T6SS Effector EvpP Prevents NLRP3 Inflammasome Activation by Inhibiting the Ca2+-Dependent MAPK-Jnk Pathway

Abstract: Inflammasome activation is an important innate immune defense mechanism against bacterial infection, and in return, bacteria express virulence determinants that counteract inflammasome activation. Many such effectors are secreted into host cells via specialized bacterial secretion systems. Here, the intracellular pathogenic bacterium Edwardsiella tarda was demonstrated to activate NLRC4 and NLRP3 inflammasomes via a type III secretion system (T3SS), and to inhibit NLRP3 inflammasome via a type VI secretion sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
104
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 142 publications
(109 citation statements)
references
References 49 publications
4
104
0
Order By: Relevance
“…We found that R3 markedly inhibited the NF-κB and MAPK pathway in vitro and in vivo, which are known activators of the NLRP3 inflammasome and have been recognized as atherogenic mechanisms, 26,[40][41][42] suggesting R3 could inhibit the priming signal of the NLRP3 inflammasome. Attenuation of NF-κB and MAPK pathways by R3 treatment would account for the lower expression of inflammatory cytokines detected in our study, including IL-6 and TNF-α.…”
Section: Discussionmentioning
confidence: 85%
“…We found that R3 markedly inhibited the NF-κB and MAPK pathway in vitro and in vivo, which are known activators of the NLRP3 inflammasome and have been recognized as atherogenic mechanisms, 26,[40][41][42] suggesting R3 could inhibit the priming signal of the NLRP3 inflammasome. Attenuation of NF-κB and MAPK pathways by R3 treatment would account for the lower expression of inflammatory cytokines detected in our study, including IL-6 and TNF-α.…”
Section: Discussionmentioning
confidence: 85%
“…However, evpP located right before the T6SS operon is transcriptionally regulated by the ferric uptake regulator (Fur) protein by binding to the fur box upstream of evpP promoter (Santander, Golden, Wanda, & Curtiss, 2012). In Edwardsiella piscicida, T6SS chaperone EvpC binds the disordered region of evpP that assists for translocation of evpP, particularly targeting the inflammasome activation in macrophages (H. Chen et al, 2017;Hu, Anand, Sivaraman, Leung, & Mok, 2014). Regulation of evpP in E. piscicida includes temperature, pH, Mg 2+ , inorganic phosphate, and iron concentration (Chakraborty et al, 2010;Chakraborty, Sivaraman, Leung, & Mok, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…tarda ), an enteric pathogen infecting hosts from fish to human [2829], was used to identify mutants that induced significantly increased pyroprosis in HeLa cells. Compared to the wild-type strain (EIB202), one of the mutants (0909I) greatly increased LDH release (Figs S1A and 1A) and IL-18 secretion (Fig 1B), accompanied by significantly induced caspase-4 activity (Fig 1C) in HeLa.…”
Section: Resultsmentioning
confidence: 99%